Locating regions of interest prior to X-ray imaging using stereo-photogrammetry - Kulkarni, Radhika (Department of Medicine, 2015)
The research project aims at locating regions of interest (ROIs) on human subjects prior to X-ray imaging on the Lodox Statscan whole body imaging system.